Analysis of rainfall pattern change in Bangkok and Jakarta - Kusumastuti, Cilcia; Clemente, Roberto S.; Sutat Weesakul; Babel, Mukand Singh; Perret, Sylvain Roger; The Netherlands (Pathum Thani, Thailand : Asian Institute of Technology, 2009)
Vulnerability on climate change and its impacts to rainfall in Southeast Asian countries leads many studies to be conducted. Statistical analysis generally used to analyze the change in precipitation with limitation. So that, other methods such us signal processing method was used to compute return period of rainfall and their amplitude. Information of return period of rainfall and the changing of the pattern was important to be consideration for decision making on water resources planning. This study was conducted for two big cities in Southeast Asia: Bangkok and Jakarta. Urbanization in Bangkok was also one consideration to observe the rainfall pattern change. Analysis stability of mean by using t-test was done to observe the change in precipitation in Bangkok and Jakarta. From statistical analysis with 95% confident level, it showed the increasing trend of rainfall throughout Bangkok during 1969 - 2006 and increasing trend throughout Jakarta, except area in Central Jakarta during 1980 - 2002. A total 11 extreme precipitation indices from manual of 'RClimDex' and 3 newly introduced extreme precipitation indices for tropical monsoon countries were analyzed by using Mann(S1(BKendall's test. It showed the number of consecutive wet days in Bangkok tends to increase and significantly increase in the area near by Bang Na station during 1969 - 2007. It corresponded to the decreasing trend of consecutive dry days in the whole Bangkok. The number of heavy and very heavy rain days was observed significantly increase in May at by Bang Na and Don Muang Station and the reduction of rainfall days at Don Muang station in December. This showed the extension of dry season in Don Muang which is in north of Bangkok. In Jakarta, the number of consecutive dry days tends to increase during 1980 - 2002 and corresponds to the decrease in consecutive wet days except in the area around Tanjung Priok Station which was near by the sea. Analysis of newly introduced extreme precipitation indices, which are R60, R80, and RI00 for monsoon countries showed the significant change in R60 and R80 in rainy season in Bangkok and R80 in rainy season in Jakarta. Wavelet analysis was used to observe return period of rainfall in Bangkok and Jakarta. The result showed that Bangkok received less rainfall every 2 decades, whereas Jakarta, it showed continuous large amount of rainfall during the year from 1980 - 1997. Finally, this research also provided information on occurrence of urbanization in Bangkok and its impact on rainfall. The result shows the heaviest rainfall during 1991 - 2007 occurred in sub-urban area, mostly in eastern Bangkok not in the city core of Bangkok which consumed high electricity and had higher temperature compared to the sub-urban area. The spatial distribution in Bangkok did not show any strong direct relation with urbanization. More data related to parameter of urbanization and hydrological variable should be systematically collected and be analyzed for long-terms
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering inWater Engineering and Management
Thesis (M.Eng.) - Asian Institute of Technology, 2008
Keywords: Rain and rainfall -- Thailand -- Bangkok; Rain and rainfall -- Indonesia -- Jakarta